STUDIES ON THE PHYTOPLANKTON OF THE WEST COAST OF INDIA Part III. Seasonal Variation of tlie Phyteplankters and Environmental Factors - Subrahmanyan, R; Sarma, A H Viswanatha (Indian Journal of Fisheries, 2016)
IN this part of the studies, the seasonal distribution of the constituent elementsof the phytoplankton as also the meteorological and hydrologicalconditions during the conceraed period are presented based on data gatheredover a period of five years by examination by the senior author of over 1,000samples of plankton collection.The methods employed have already been described in Parts I and IIof this series (Subrahmanyan, 1959 a, b), and a list of species recorded onthe west coast may be had from Subrahmanyan (1958 b). It may be pointedout here that the compilation given here of the various species is based onenumeration data only.